2022
DOI: 10.1038/s41598-021-04233-4
|View full text |Cite
|
Sign up to set email alerts
|

Conventional dose versus dose escalated radiotherapy including high-dose-rate brachytherapy boost for patients with Gleason score 9–10 clinical localized prostate cancer

Abstract: As several recent researches focus on the importance of Gleason 9–10, we examine the role of radiotherapy dose escalation in those patients. We analyzed 476 patients with Gleason score 9–10 prostate cancer treated with radiotherapy. Of them, 127 patients were treated with conventional-dose external beam radiotherapy (Conv RT) and 349 patients were treated with high-dose radiotherapy (HDRT; 249 patients received high-dose-rate brachytherapy boost + external beam radiotherapy [HDR boost] and 100 patients receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Two studies directly compared OS after EBRT and EBRT + BT. There was a trend toward improved OS with BT boost (HR = 0.86; p = 0.08), but this was heavily weighted towards Kishan et al with only a minor contribution from Yamazaki et al (not shown) [14] , [22] .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Two studies directly compared OS after EBRT and EBRT + BT. There was a trend toward improved OS with BT boost (HR = 0.86; p = 0.08), but this was heavily weighted towards Kishan et al with only a minor contribution from Yamazaki et al (not shown) [14] , [22] .…”
Section: Resultsmentioning
confidence: 96%
“…A total of eight studies were selected for inclusion in the meta-analysis, all of which were retrospective series classified as Level 4 evidence [14] , [20] , [21] , [22] , [23] , [24] , [25] , [26] . Four reported data from a single institution, while the remaining four were multi-institutional.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation